Double-leg attack vs. arm-drag: Examining muscle synergy consistency between elite and sub-elite freestyle wrestlers - Beinabaji, H.; Eslami, M.; Hosseininejad, S. E.; Esmaili Paeen Afrakoti, I.; Fayyaz Movaghar, A. (Journal of Biomechanics, 2025)
The ability to execute coordinated muscle contractions has significant implications for wrestlers` performance. The skill level of the individual and the type of technique chosen may influence their success in wrestling. The purpose of this study was to investigate the effect of wrestler skill level (elite vs. sub-elite) on the consistency of muscle synergies during the execution of the Double-Leg Attack and Arm-Drag techniques in freestyle wrestling. Thirty-four male junior wrestlers, classified as either elite (n = 17) or sub-elite (n = 17), participated in the study. Surface electromyography (EMG) recordings from five upper limb muscles were used to extract muscle synergies via Non-negative Matrix Factorization (NMF). Synergy consistency was assessed using Cosine Similarity (CS) analysis. A significant interaction effect was found between skill level and technique type on the consistency of the first muscle synergy (p = 0.05), with the Elite group demonstrating greater spatio-temporal synergy consistency compared to the Sub-elite group during the execution of the Double-Leg Attack technique. Elite wrestlers also demonstrated higher temporal consistency in the middle and explosive phases of both techniques. The Double-Leg Attack technique showed more consistent muscle activation patterns than the Arm-Drag, regardless of skill level. These findings suggest that a wrestler`s training experience and skill level significantly influence their ability to effectively execute wrestling techniques by optimizing neuromuscular control strategies. Sport medicine practitioners and athletic trainers may consider monitoring alterations in the muscle synergy components throughout training and rehabilitation programs. This approach could provide a means to objectively assess and benchmark changes in neuromuscular coordination.